The Use of stem cells in burns treatment - Monika Brzozowska; Wiktoria Wardal; Natalia Furlepa; Robert Rzenno; Karolina Wojciechowska; Marcelina Matuszewska; Katarzyna Wicha; Natalia Sidz; Magdalena Tomaszewska; Wiktoria Jedlikowska (Journal of Education, Health and Sport)
Introduction and purpose: Burns are a real problem that can result in long hospitalization and scarring. Stem cells (SCs) have been shown to have a number of actions that accelerate and improve the healing process. The aim of this review is to explore the stem cell mechanisms that can be used to improve burn healing